EXPLORING RURAL STUDENTS’ ACCEPTANCE OF AI FOR ENGLISH SPEAKING: UNCOVERING PRIVACY AS A SUPPORTING FACTOR - Fajri Habibi; Rendy Yudha Pratama; Soviatun Khovivah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This study explores rural students’ acceptance of Stimuler, an AI-based mobile application designed to support English language speaking skills. Using a mixed-methods approach grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT) and psychological constructs, the study involved 29 students from a rural junior high school. Quantitative data were collected through Likert-scale questionnaires, while open-ended responses provided qualitative insights. Results indicate that students hold generally positive perceptions toward the application, particularly regarding performance expectancy, ease of use, and its potential to enhance speaking proficiency. However, challenges such as inconsistent internet access and limited teacher engagement with digital tools were identified.A notable secondary finding of the study is the role of privacy in influencing students’ comfort with AI-based assessments. Although not a primary focus, privacy emerged as a significant supporting factor contributing to student confidence and engagement. Students expressed that feeling secure about their personal data positively affected their willingness to participate in speaking activities. This aligns with prior studies emphasizing privacy's role in trust and learner well-being. The study highlights the importance of addressing both technological and psychological dimensions when implementing AI in under-resourced educational contexts.